2020
DOI: 10.1093/ageing/afaa015
|View full text |Cite
|
Sign up to set email alerts
|

What is important to people with dementia living at home? A set of core outcome items for use in the evaluation of non-pharmacological community-based health and social care interventions

Abstract: Abstract Objectives inconsistency in outcome measurement in dementia care trials impedes the comparisons of effectiveness between trials. The key aim of this study is to establish an agreed standardised core outcome set (COS) for use when evaluating non-pharmacological health and social care interventions for people with dementia living at home. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
98
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(99 citation statements)
references
References 23 publications
(32 reference statements)
1
98
0
Order By: Relevance
“…In a review of outcome measures used in dementia trials and mild cognitive impairement, the authors found that of the 805 identified trials, cognitive outcomes were reported in 70 % while outcomes of quality of life were reported in 12 % (Harrison, Noel-Storr, Demeyere, Reynish & Quinn, 2016). Interestingly, cognitive outcomes have been identified as less important and outcomes of wellbeing as most important by people with dementia and partners (Reilly et al, 2020). Furthermore, the primary threatening aspects for couples living with dementia are described as "losses", such as loss of roles in a relationship and loss of couple identity (Davies et al, 2011).…”
Section: Meaningfulness Of Couple-centred Interventionsmentioning
confidence: 99%
“…In a review of outcome measures used in dementia trials and mild cognitive impairement, the authors found that of the 805 identified trials, cognitive outcomes were reported in 70 % while outcomes of quality of life were reported in 12 % (Harrison, Noel-Storr, Demeyere, Reynish & Quinn, 2016). Interestingly, cognitive outcomes have been identified as less important and outcomes of wellbeing as most important by people with dementia and partners (Reilly et al, 2020). Furthermore, the primary threatening aspects for couples living with dementia are described as "losses", such as loss of roles in a relationship and loss of couple identity (Davies et al, 2011).…”
Section: Meaningfulness Of Couple-centred Interventionsmentioning
confidence: 99%
“…Whilst many studies demonstrate that people with dementia can give reliable accounts of their life using existing dementia-specific QoL/HRQoL self-report instruments [1,2], such measures do not capture the full range of psychosocial outcomes that people with dementia themselves consider important, such as autonomy [3]. Recent studies on how people with dementia might live well with the condition indicate that asset-based factors such as self-efficacy and humour contribute significantly to overall well-being [4,5]. These factors are closely aligned to the concept of well-being but are not fully captured by traditional Qol/HRQoL instruments.…”
Section: Introductionmentioning
confidence: 99%
“…This will not come as a surprise as the MMSE has become synonymous with dementia trials, but what is surprising is that the MMSE was not designed as an outcome measurement instrument and, as Harrison et al (2016) state in their review of outcome measurement instruments, its psychometric properties are poorly or often not described. On the other hand, concepts around the quality of life and social health are greatly valued by people living with dementia and other key stakeholders (Reilly et al, 2020), and yet these outcomes are used far less frequently (Harrison et al, 2016;Couch et al, 2020). For example, quality of life has only been included in 13% of trials (Harrison et al, 2016).…”
Section: Stakeholder Involvementmentioning
confidence: 99%
“…question tends to be addressed by a multiphase and mixedmethods study design including using literature reviews and qualitative research to elicit a "longlist" of existing and new outcomes of interest (Harding et al, 2019). It is then recommended to use consensus methods such as Delphi surveys and consensus workshops to identify the most importantor coreoutcomes (Reilly et al, 2020). The involvement of key stakeholders throughout is key because then the core outcomes will be aligned to the priorities of key stakeholders, including people living with dementia and family carers (Morbey et al, 2019).…”
Section: Stakeholder Involvementmentioning
confidence: 99%
See 1 more Smart Citation